AKTIVITAS ANTIJAMUR EKSTRAK ETANOL dan FRAKSI DAUN KEMANGI (Ocimum Sanctum L.) TERHADAP JAMUR Candida albicans, Microsporum gypseum, dan Aspergillus flavus - Ika Kurnia Sukmawati (JURNAL FARMASI GALENIKA, 2016)
Kemangi (Ocimum sanctum) has been widely used by people to treat various diseases, such as bloating or cold, fever, rheumatism, ulcers. The aim of this study was to determine the antifungal activity of extract and fractions of Kemangi leaves. The extract obtained in this study was obtainedby maceration method using ethanol 96%. The fraction was using an ethyl acetate, n-hexane and water as a solvent. Antifungal test was performed by broth microdilution method to determine the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) toward the fungus of Candida albicans, Aspergillus flavus and Microsporum gypseum at concentrations of 2, 4, 8, 16, 32, 64, 128, 256, 512, 1024 µg/mL. The result of this research showed that extract and fractions of kemangi leaves had antifungal activity with MIC value against fungal of Microsporum gypseum extractwas 512 µg/mL, against the fungus of Candida albicans and Aspergillus flavus showed MIC 1024 µg/mL. Water fractions tested on fungal of Microsporum gypseum showed MIC values of 512 µg/mL, the fraction of nhexane and acetate ethyl showed MIC 1024 µg/mL. The research was continued by observing the morphology with scanning electron microscope (SEM).The results showedMicrosporumgypseumunder normal circumstanceshad asmooth surface, whereasthe presenceof ethanol extractof basilconsentras i4x MICmakesshrink the cell surface.